PM2.5 and CO Concentrations from Peatland Forest fires 2023 in Central Kalimantan, Indonesia - Kitso Kusin; Patricia E. Putir; Sampang Gaman; Alpian; Wahyu Supriyati; Adi Jaya (Poltanesa, 2025)
Peatland Forest fires are one of the main causes of high concentrations of particulate matter and gases, especially PM2.5 and carbon monoxide (CO). Particles of PM2.5 are very small, so they can enter directly into the human lungs, as well as high concentrations of CO will affect the concentration of carboxyhemoglobin (COHb) in human blood, so it can cause decreased vision, hearing, and death. Monitoring of particulate and gas concentrations is carried out, to increase the concern of all levels of society, so as not to burn forests and peatlands in the dry season, be careful in carrying out all activities outside the home during peatland forest fires, especially vulnerable ages such as infants, children, pregnant, people with congenital diseases and the elderly. The sensor tools used are P-Sensor for recording PM2.5 concentration and EL-USB-CO sensor for recording carbon monoxide (CO) concentration placed at UPT Laboratorium Lahan Gambut – CIMTROP University of Palangka Raya and north-west at PERUM PEMDA Km 10 Cilik Riwut, Palangka Raya for 2 months during forest and peatland fires in September and October 2023. Data is tabulated and analyzed using Microsoft Excel. T-test result of PM2.5 and CO concentration during the rainy season and dry season (peatland forest fire) is p-value < 0,05 at UPT LLG – CIMTROP dan Perum Pemda Km 10 Cilik Riwut. The PM2.5 concentration in UPT LLG – CIMTROP during the peatland forest fires 2023 is 700.24 μg/m3, while the CO concentration is 7,446 μg/m3 (6.5 ppm). The PM2.5 concentration at the PERUM PEMDA Km 10 Cilik Riwut is 333.39 μg/m3, while the CO concentration is 26,439 μg/m3 (23 ppm). PM2.5 concentrations in UPT LLG – CIMTROP are higher, but CO concentrations are lower than those in PERUM PEMDA Km. 10 Cilik Riwut, possibly caused by wind direction effect, vegetation, fuel, and other sources such as vehicle fumes in respective locations.